Pengembangan Sistem Aplikasi Penjadwalan Pendampingan Mahasiswa Disabilitas (Studi Kasus: Pusat Studi dan Layanan Disabilitas Universitas Brawijaya) - Dama Yuliana; Bayu Priyambadha; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Scheduling is a process by which time is fully divided according to the activities carried out. However, the scheduling process that is not carried out properly will cause problems like what happened at the Disability Study and Service Center Brawijaya University (PSLD)r. The process of completing the schedule currently carried out in PSLD is by selling so that it is found a schedule that conflicts with human error factors. In addition, the scheduling system is still difficult to change volunteers. Volunteers offered cannot provide assistance. Therefore, this study aims to develop a scheduling system that can minimize human error and make it easier to make volunteer changes. System development is carried out through several stages, namely: needs analysis, design, implementation, and system testing. System development is done by object oriented learning. The software development method used is a prototype with 2 iterations. The system implementation is carried out using the PHP programming language with the help of the CodeIgniter and Bootstrap framework. Testing is done by testing the white box testing with unit testing using the basic path testing method and black box testing with validation testing. The results of this study indicate that the system is implemented in accordance with user requirements that have been determined, shown from the results of unit testing and validation testing of 100% valid